PEMBERDAYAAN IBU-IBU PKK DESA TUYUHAN, KECAMATAN PANCUR, KABUPATEN REMBANG MELALUI PENDAMPINGAN RINTISAN USAHA - Damayanti, Damayanti; Sodiq, Fajar; Sa'diyyah, Halimatus; Maula, Hazizatul; Widowati, Madurento (Fokus ABDIMAS, 2024)
Community empowerment is an effort to prepare the community along with steps to strengthen community institutions to be able to realize progress, independence, and prosperity in an atmosphere of sustainable social justice. The Community Service Team formulated the problems faced by Partners, namely: 1). Many PKK mothers do not know about entrepreneurship, 2). Lack of business motivation, and 3). Knowledge of business management is still low. Based on these problems, the Community Service Team tries to help solve problems including providing business motivation and introduction to entrepreneurship, business management training, training and coaching for fish processing innovation, as well as evaluation and mentoring for Partners. After this service is carried out, it is hoped that family economic income will increase and be more prosperous. Keyword: empowerment, pioneering business, family walfare